The anthropology of cultural performance - Lewis, John Lowell (Palgrave Macmillan, 2013)
Contemporary life in most large-scale societies is not truly cultural, in the strong sense, but rather merely 'culture-like.' Using a semeiotic phenomenological approach based on the work of philosopher C.S. Peirce, Lewis presents a framework for understanding performative events in any cultural life-world. By revisiting Victor Turner's work on ritual and engaging with those who have built upon his ideas, the book presents a program for making connections between intimate embodied habits and major cultural practices in a given social setting. Beginning with a distinction between special events and everyday life, Lewis examines fundamental event types including play, ritual, work, and carnival.